Fucoidan Alleviates Renal Fibrosis in Diabetic Kidney Disease via Inhibition of NLRP3 Inflammasome-Mediated Podocyte Pyroptosis - Wang, Mei-Zi; Wang, Jie; Cao, Dong-Wei; Tu, Yue; Liu, Bu-Hui; Yuan, Can-Can; Li, Huan; Fang, Qi-Jun; Chen, Jia-Xin; Fu, Yan; Wan, Bing-Ying; Wan, Zi-Yue; et al. (Frontiers in Pharmacology, 2022)
Background: Fucoidan (FPS) has been widely used to treat renal fibrosis (RF) in patients with diabetic kidney disease (DKD); however, the precise therapeutic mechanisms remain unclear. Recently, research focusing on inflammation-derived podocyte pyroptosis in DKD has attracted increasing attention. This phenomenon is mediated by the activation of the nucleotide-binding oligomerization domain (Nod)-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome, leading to RF during DKD progression. Therefore, we designed a series of experiments to investigate the ameliorative effects of FPS on RF in DKD and the mechanisms that are responsible for its effect on NLRP3 inflammasome-mediated podocyte pyroptosis in the diabetic kidney. Methods: The modified DKD rat models were subjected to uninephrectomy, intraperitoneal injection of streptozotocin, and a high-fat diet. Following induction of renal injury, the animals received either FPS, rapamycin (RAP), or a vehicle for four weeks. For in vitro research, we exposed murine podocytes to high glucose and MCC950, an NLRP3 inflammasome inhibitor, with or without FPS or RAP. Changes in the parameters related to RF and inflammatory podocyte injury were analyzed in vivo. Changes in podocyte pyroptosis, NLRP3 inflammasome activation, and activation of the adenosine monophosphate-activated protein kinase (AMPK)/mammalian target of rapamycin complex 1 (mTORC1)/NLRP3 signaling axis involved in these changes were analyzed in vivo and in vitro. Results: FPS and RAP ameliorated RF and inflammatory podocyte injury in the DKD model rats. Moreover, FPS and RAP attenuated podocyte pyroptosis, inhibited NLRP3 inflammasome activation, and regulated the AMPK/mTORC1/NLRP3 signaling axis in vivo and in vitro. Notably, our data showed that the regulative effects of FPS, both in vivo and in vitro, on the key signaling molecules, such as p-AMPK and p-raptor, in the AMPK/mTORC1/NLRP3 signaling axis were superior to those of RAP, but similar to those of metformin, an AMPK agonist, in vitro. Conclusion: We confirmed that FPS, similar to RAP, can alleviate RF in DKD by inhibiting NLRP3 inflammasome-mediated podocyte pyroptosis via regulation of the AMPK/mTORC1/NLRP3 signaling axis in the diabetic kidney. Our findings provide an in-depth understanding of the pathogenesis of RF, which will aid in identifying precise targets that can be used for DKD treatment.